2019
DOI: 10.3329/bmjk.v51i1-2.40469
|View full text |Cite
|
Sign up to set email alerts
|

Emerging threat in antifungal resistance on superficial dermatophyte infection

Abstract: Background: Dermatophytosis are most common fungul infection globally and according to WHO the prevalence is about 20-25% and does not spare people of any race or age. Over the past few years antifungal resistance has been emerged due to irrational use of antifungal drugs in cutaneous mycosis. Objective: The aim of the study is to evaluate the efficacy of different antifungul drugs (Terbinafin. Fluconazole, Itraconazole, Griseofulvin) on superficial mycosis depending on various factors. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Least drug resistance was found with terbinafine. 11 We had parallel findings with a study by Singh et al who found that itraconazole is the most effective drug, followed by fluconazole (daily), terbinafine and then griseofulvin in chronic and chronic relapsing dermatophytosis in India. 12 In a study done on a patient with long term recurrent tinea corporis by Ardeshna et al isotretinoin(20 mg/day) was combined with itraconazole (200 mg/day).…”
Section: Fluconazolesupporting
confidence: 82%
“…Least drug resistance was found with terbinafine. 11 We had parallel findings with a study by Singh et al who found that itraconazole is the most effective drug, followed by fluconazole (daily), terbinafine and then griseofulvin in chronic and chronic relapsing dermatophytosis in India. 12 In a study done on a patient with long term recurrent tinea corporis by Ardeshna et al isotretinoin(20 mg/day) was combined with itraconazole (200 mg/day).…”
Section: Fluconazolesupporting
confidence: 82%
“…affected. 3,9,[10][11][12][13] The predisposition of infection among adults may be attributed to their greater physical activity, mobility, and perspiration that aids in the proliferation of the fungus. Previous studies reported the association of recurrent dermatophytosis with various risk factors such as occupation, family history of dermatophytosis, preexisting comorbidity, excessive sweating, type of undergarments (tight fit), poor frequency of washing clothes, sharing of a towel/clothes, frequency of taking baths, and prior use of topical steroids.…”
Section: Age Distributionmentioning
confidence: 99%